THE EFFECT OF SERVICE QUALITY AND CORPORATE IMAGE ON CUSTOMER SATISFACTION AND LOYALTY OF THE CARGO TERMINAL AT SAMS SEPINGGAN AIRPORT BALIKPAPAN DURING THE COVID-19 PANDEMIC - Thamrin, Muhammad; Harwani, Yuli (Dinasti Publisher, 2022)
This study aims to analyze the effect of service quality and corporate image on customer satisfaction and loyalty at the cargo terminal at SAMS Airport, Balikpapan. This study uses a quantitative positivism paradigm which is used to determine the relationship between variables. Data were taken using a questionnaire method given to 120 respondents with a purposive sampling technique. The data analysis method used is Structural Equation Modeling (SEM) - Partial Least Square (PLS). The results of research with 6 careful hypotheses include service quality has a positive and significant effect on customer satisfaction, corporate image has a positive and significant influence on customer satisfaction, service quality has a positive and significant influence on corporate image, service quality has no positive and significant effect on customer loyalty, corporate image has no positive and significant effect on customer loyalty, and customer satisfaction has a positive and significant effect on customer loyalty.